Compact liquid cooling strategy with phase change materials for Li-ion batteries optimized using response surface methodology. (15th October 2018) - Ling, Ziye; Cao, Jiahao; Zhang, Wenbo; Zhang, Zhengguo; Fang, Xiaoming; Gao, Xuenong
Highlights: A hybrid battery cooling system is optimized with response surface methodology. PCM composition is optimized along with the active cooling structure. Effects of battery layout, PCM composition and cooling intensity are studied. A compact cooling strategy with composite PCM and liquid cooling is presented. The PCM mass and volume have been reduced by 94.1% and 55.6% per battery cell. Abstract: The hybrid system that integrates active cooling into phase change materials (PCMs)/expanded graphite (EG) shows great prospects for power battery thermal management. But because of the heavy weight, the system need to be optimized with a balance of the cooling capacity contributed by the active and passive cooling. This study develops an optimization method based on the response surface methodology (RSM) and a numerical heat transfer model to minimize the weight and volume of such a battery thermal management system. With the PCM thermo-physical property models incorporated, the method can optimize the PCM composition along with the active cooling structure – taking the contributions of both the active and passive cooling into account. We minimize the PCM mass of the system with this method, and analyze the effects of the PCM composition, the battery module layouts and the active cooling configuration on the thermal management performance. Then we present an optimal design for this hybrid thermal management system, which helps save the PCM mass by up to 94.1% and the volume by up to 55.6%. The thermal management performance of the design is verified with an experiment. The results show the maximum battery temperature in a 20-battery module during the 1.5C discharge is limited to 37.0 °C while the maximum temperature difference is limited to be smaller than 3 °C. Compared with the conventional liquid cooling system, the hybrid system is not only highly efficient, but lightweight, with simple structure and flexible to the batteries with arbitrary shapes.